Airway management by the general practitioner in trauma patients. Technical and non-technical skills (2016)
General practitioners must constantly face challenges imposed by their profession when performing interventions that are necessary for their patients. Many of these interventions not only require proper use of theoretical knowledge, but also putting into practice non-technical and psychomotor skills developed through professional training. Given the specific characteristics of each patient, the clinical setting in the which procedure takes place and the limited skills of the professional, the management of the airway of a patient with trauma injuries in the emergency room represents a major challenge for physicians.